Zimbabwe's popular music industry and copyright legislation - Mhiripiri, Joyce T.; Mhiripiri, Nhamo A. (Taylor & Francis (Routledge); UNISA Press [Copublisher], 2016)
This article explores the potential for growth in Zimbabwean musicians’ earnings through the strategic monitoring and use of their copyright and a coordinated collection of royalties. Zimbabwean popular music is now big business and employs large numbers of people, with many more aspiring to join the industry. Policies have been put into place in the last few years in an attempt to grow the music industry and these have had remarkable effects on the emergence of many new musical acts. This article suggests that there is widespread misunderstanding and ignorance of copyright law and protection in Zimbabwe, but that the onus is on artists to protect their own copyright, given the scant resources of national organisations.